RHIZOSPHERE MICROORGANISMS AND PHOSPHORUS AVAILABILITY FOR PLANTS - & Majeed, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Phosphorus (P) is one of the major plant nutrients that directly or indirectly affect all biological processes. It is a key component of energy metabolism, and biosynthesis of nucleic acids and membranes. Phosphorus deficiency is considered to be one of the major limitations for crop production particularly in low-input agriculture systems around the world and nearly 80% of applied mineral P may be retained in the soil. Roots provide an interface for P moving from one living system—the soil—into another living system—the plant. Microbial processes in soil are important for the distribution of P between various inorganic and organic P fractions and subsequently for the potential availability of phosphate for plant absorption. These processes are predominantly manifest within the rhizosphere where readily-available C substrates are most abundant. So this review, focus on the contribution of soil microorganisms on the plant P nutrition through their capacity to increase the availability of soil P and its subsequent uptake by plants.